International market entry strategies by Malaysian construction firms / Che Khairil Izam Che Ibrahim, Jazuri Abdullah and Muhammad Hafeez Osman - Che Ibrahim, Che Khairil Izam; Abdullah, Jazuri; Osman, Muhammad Hafeez (2009)
Globalization by definition involves trans-boundary activities. Globalization frequently translates into creation of new construction markets. Focusing on the entry strategies is one of the important dimensions of the process of internationalization of Malaysian construction firms. In securing the position in the international market, Malaysian construction firms need to consider the influence of numerous factors both internal and external to the firm in deciding when to enter a market. The need for the strategic planning is to keep track of firm's operations in a continuously changing international environment. This study focuses on developing a conceptual framework for internationalization process to facilitate more Malaysian construction firms to venture in the international market and to highlight the importance of the factors involved in this process. Twenty eight (28) respondents from Class A and Grade 7 construction firms were received to get their opinions on the strategic entry decision making in exploring international markets. The empirical results show quality, project management capability, equipment, material and labour support are the most important strength: currency fluctuation, shortage of financial, interest rate increase are the most important threats relative to international market: opening up new markets, technological advancement, increase profitability are the most important opportunities available in international works. This study has developed a new conceptual framework that includes the identified elements influencing decision making to international market. The framework is a multi phase because it includes all the steps in strategy formulation with internal and external environment scanning. The strategy of the framework based on firm mission, vision and goals; company resources and capabilities; external environment in international construction; location considerations for specific country and locale; entry timing for going abroad and entry mode choice. This study’s results are of relevance to Malaysian construction firms as it illustrates the determination of entry strategies and factors affecting venturing the incremental internationalization and hence enhancing relationship between firms across national borders. This study has shown that the possibility of Malaysian construction companies to penetrate international market and recognised as global players especially in Middle East, South and Southeast Asian region are expected to increase and higher near the future if identified threats and challenges can be handled and controlled by using the right strategic decision tools.